Ulinastatin alleviates mitochondrial damage and cell apoptosis induced by isoflurane in human neuroglioma H4 cells. (October 2020) - Lin, D; Zhu, X; Li, J; Yao, Y; Guo, M; Xu, H
Isoflurane has been demonstrated to induce mitochondrial damage and cell apoptosis. The isoflurane-induced inflammation may be an important reason for this phenomenon. Studies have shown that ulinastatin (UTI) has an anti-inflammatory effect. Our aim was to investigate whether UTI could attenuate isoflurane-induced mitochondrial damage and cell apoptosis by inhibiting inflammation. Human neuroglioma H4 cells were exposed to isoflurane with or without UTI. The ratio of cell apoptosis was evaluated by flow cytometry. β-Amyloid (Aβ) peptide and cleaved caspase 3 expression were evaluated by Western blot analysis. The concentrations of tumor necrosis factor α (TNF-α) and interleukin 1β (IL-1β) were detected by sandwich enzyme-linked immunosorbent assays. Mitochondrial structural changes were detected by transmission electron microscopy. Mitochondrial membrane potential (Δψm) was determined by 5, 5′, 6, 6′-Tetrachloro-1, 1′, 3, 3′-tetraethyl-imidacarbocyanine iodide (JC-1). The activity of the mitochondrial electron transport chain (ETC) complexes I, II, III, and IV was determined by assay kits. UTI attenuated the TNF-α and IL-1β release induced by isoflurane. UTI could also reduce mitochondrial structure damage, mitigate the decrease in Δψm, and improve ETC complexes dysfunction. Furthermore, it decreased cell apoptosis induced by isoflurane in H4 cells. UTI had no effect on isoflurane-induced Aβ expression. UTI may mitigate isoflurane-induced mitochondrial damage and cytotoxicity by inhibiting inflammation.